This problem is a follow-up to "Sum 1" , my previous problem; if you've read my solution to "Sum 1", this problem should be straightforward.
Evaluate:
n = 1 ∑ ∞ ( n ( − 1 ) n k = 1 ∑ n ( k ( − 1 ) k ) )
The answer can be expressed as 6 a 2 π a 1 + a 5 ( ln a 3 ) a 4 , where a 1 , a 2 , a 3 , a 4 , and a 5 are prime positive integers; find 1 0 0 0 0 a 1 + 1 0 0 0 a 2 + 1 0 0 a 3 + 1 0 a 4 + a 5 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice. In fact, it has been pointed out to me that there is an easy way to solve this without dilogarithm. By switching the order of summation and then switching the letters back: S = n = 1 ∑ ∞ ( n ( − 1 ) n k = 1 ∑ n ( k ( − 1 ) k ) ) = n = 1 ∑ ∞ ( n ( − 1 ) n k = n ∑ ∞ ( k ( − 1 ) k ) ) Then just add them together! 2 S = n = 1 ∑ ∞ ( n ( − 1 ) n ( k = 1 ∑ ∞ ( k ( − 1 ) k ) + n ( − 1 ) n ) ) = n = 1 ∑ ∞ ( ( n ( − 1 ) n ) 2 ) + ( n = 1 ∑ ∞ ( n ( − 1 ) n ) ) 2 so 2 S = 6 π 2 + ln 2 2 → S = 1 2 π 2 + 2 ln 2 2 .
Define the function F ( x ) : F ( x ) : = n = 1 ∑ ∞ ( n 1 k = 1 ∑ n ( k ( − 1 ) k ) ( x − 1 ) n ) Note that F ( 1 ) = 0 and F ( 0 ) is the answer to the problem.
Taking the derivative, we have: F ′ ( x ) = n = 0 ∑ ∞ ( k = 1 ∑ n + 1 ( k ( − 1 ) k ) ( x − 1 ) n ) and through a very similar series of steps to that in my solution to "Sum 1" , we can simplify the above expression to: F ′ ( x ) = ( x − 1 ) ( x − 2 ) ln x Thus (since F ( 1 ) = 0 ): F ( x ) = F ( 1 ) + ∫ 1 x ( ( t − 1 ) ( t − 2 ) ln t d t ) = ∫ 1 x ( ( t − 1 ) ( t − 2 ) ln t d t ) and the answer to the problem is F ( 0 ) : F ( 0 ) = ∫ 1 0 ( ( t − 1 ) ( t − 2 ) ln t d t ) = − ∫ 0 1 ( ( t − 1 ) ( t − 2 ) ln t d t ) In the solution to the original problem, I alluded to the possibility of solving it using the dilogarithm function ; here, the dilogarithm function is necessary: ∫ 0 1 ( ( t − 1 ) ( t − 2 ) ln t d t ) = dilog ( 2 1 ) − 6 π 2 However, dilog ( 2 1 ) is a special value of the dilogarithm function: dilog ( 2 1 ) = 1 2 π 2 − 2 ln 2 2 In summary, we have shown that: n = 1 ∑ ∞ ( n ( − 1 ) n k = 1 ∑ n ( k ( − 1 ) k ) ) = F ( 0 ) = − ∫ 0 1 ( ( t − 1 ) ( t − 2 ) ln t d t ) = − ( dilog ( 2 1 ) − 6 π 2 ) = − ( ( 1 2 π 2 − 2 ln 2 2 ) − 6 π 2 ) = 1 2 π 2 + 2 ln 2 2 and the answer is 1 0 0 0 0 ⋅ 2 + 1 0 0 0 ⋅ 2 + 1 0 0 ⋅ 2 + 1 0 ⋅ 2 + 2 = 2 2 2 2 2 .
Problem Loading...
Note Loading...
Set Loading...
write the sum as n = 1 ∑ ∞ n ( − 1 ) n ∫ 0 − 1 x − 1 x n − 1 d x = ∫ 0 − 1 x − 1 ln ( 1 + x ) − ln ( 2 ) d x substituting x = 1 − 2 u we have ∫ 1 / 2 1 u − ln ( 1 − u ) d u = l i 2 ( 1 ) − l i 2 ( 1 / 2 ) = 1 2 π 2 + 2 ln 2 ( 2 )